From matte banded to glossy black: Structures underlying colour change in the caudal lures of southern death adders (Acanthophis antarcticus, Reptilia: Elapidae) - Jenna Crowe-Riddell (hasCollector); Kate Sanders (hasCollector)
Video of a southern death adder (Acanthophis antarcticus) caudal luring. Note that the video has been slowed down.